High-transconductance silicon carbide nanowire-based field-effect transistor (SiC-NWFET) for high-temperature applications - (:unkn) unknown (EMERALD GROUP PUBLISHING LTD, 2021)
Purpose The purpose of this study is to present a systematic investigation of the effect of high temperatures on transport characteristics of nitrogen-doped silicon carbide nanowire-based field-effect transistor (SiC-NWFET). The 3C-SiC nanowires can endure high-temperature environments due to their wide bandgap, high thermal conductivity and outstanding physical and chemical properties. Design/methodology/approach The metal-organic chemical vapor deposition process was used to synthesize in-situ nitrogen-doped SiC nanowires on SiO2/Si substrate. To fabricate the proposed SiC-NWFET device, the dielectrophoresis method was used to integrate the grown nanowires on the surface of pre-patterned electrodes onto the SiO2 layer on a highly doped Si substrate. The transport properties of the fabricated device were evaluated at various temperatures ranging from 25 degrees C to 350 degrees C. Findings The SiC-NWFET device demonstrated an increase in conductance (from 0.43 mS to 1.2 mS) after applying a temperature of 150 degrees C, and then a decrease in conductance (from 1.2 mS to 0.3 mS) with increasing the temperature to 350 degrees C. The increase in conductance can be attributed to the thermionic emission and tunneling mechanisms, while the decrease can be attributed to the phonon scattering. Additionally, the device revealed high electron and hole mobilities, as well as very low resistivity values at both room temperature and high temperatures. Originality/value High-temperature transport properties (above 300 degrees C) of 3C-SiC nanowires have not been reported yet. The SiC-NWFET demonstrates a high transconductance, high electron and hole mobilities, very low resistivity, as well as good stability at high temperatures. Therefore, this study could offer solutions not only for high-power but also for low-power circuit and sensing applications in high-temperature environments (similar to 350 degrees C).
Keywords: High-temperature nanoelectronics; high transconductance; low-power operation; SiC nanowire field-effect transistor (FET); Wide bandgap semiconductors (WBG); ELECTRICAL-TRANSPORT PROPERTIES; ELECTRONICS; OPERATION; DIAMOND; DEVICES